Analysis of the Response Law of Station Buried Depth Change to Subway Station Under Vibration Load - Chao Lin; Jiansheng Li; Yuehui Shen; Tao Liu; Baofeng Zhao; Zhenjun Liao; Lumeng Zhou; Qishan Huang; Gehong Wang; Jiaxin Chen; et al. (中国科学与技术学报, 2025)
In the period of rapid development of urban rail transit, the traditional transportation hub has become increasingly unable to meet the needs of people ’s travel due to the lack of rationality and efficiency of land use, the monotonous structure and other reasons, resulting in a series of new three-dimensional transportation hub. The Huangmugang comprehensive transportation hub in Shenzhen is a complex four-story underground station with different spans. The station adopts a large-diameter and large-angle V-column structure system. In this paper, a simplified seismic analysis method suitable for the V-pillar structure of subway station is proposed, and the two-dimensional finite element model and dynamic time history analysis of subway station are completed in combination with practical engineering cases. The influence of buried depth change of station on the response law of subway station is studied. The seismic response results of station under three different buried depths are analyzed, and the stress and deformation law of key components such as V-pillar, side wall and station floor of station structure are compared and analyzed.The main conclusions are as follows : with the increase of the buried depth of the station, the constraint effect of the surrounding soil on the station structure is obviously enhanced, which is manifested by the increase of the constraint effect of the soil on the side wall of the station and the decrease of the displacement of the side wall. However, with the further increase of the buried depth of the station, the constraint effect of the surrounding soil on the station tends to be stable. At the same time, due to the increase of the thickness of the overlying soil, the self-weight stress transmitted by the soil of the station increases, which makes the deformation of the side wall of the station increase.